Unorthodox questions of forensic identification theory (Academic Journal of Internal Affairs, 2021)
The changes that affect society as a whole, thereby criminal behavior and law enforcement toolkit, call for a necessary rethinking of previous forensic methods and theories. Identification theory, which can also be considered as the focus of forensics, plays a prominent role in this evolving system. The study sheds light on current problems by articulating a number of questions. It rejects the selfexisting conceptual and substantive unit of the theory of identification, points to the need for close interconnection of forensic theories, draws attention to the erroneous use of certain concepts, interprets the content on a wide scale and proposes a new definition.
Keywords: identification theory; trace; residue; expert identification